TURKISTONDA XIX ASR OXIRI XX ASR BOSHLARIDA MADRASA VA MAKTABLAR HAQIDA - Mustafayev Jafar Shomirzayevich; Kholmurodova Rukhshana (Journal of new century innovations, 2024)
Abstract: This article examines the state of madrassas, schools, religious houses and law schools that operated in Turkestan at the end of the 19th - beginning of the 20th century, their education system, the books taught in them, their influence. and the attitude of Tsarist Russia towards Muslim schools will be analyzed from a historical point of view.